2015
DOI: 10.1016/j.clim.2015.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to infections, without concomitant hyper-IgE, reported in 1976, is caused by hypomorphic mutation in the phosphoglucomutase 3 ( PGM3 ) gene

Abstract: Phosphoglucomutase 3 (PGM3) is an enzyme converting N-acetyl-glucosamine-6-phosphate to N-acetyl-glucosamine-1-phosphate, a precursor important for glycosylation. Mutations in the PGM3 gene have recently been identified as the cause of novel primary immunodeficiency with a hyper-IgE like syndrome. Here we report the occurrence of a homozygous mutation in the PGM3 gene in a family with immunodeficient children, described already in 1976. DNA from two of the immunodeficient siblings was sequenced and shown to en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 26 publications
1
33
0
Order By: Relevance
“…We review here the history of HIES, and what is currently known about its three proposed genetic forms, and we discuss the contribution of the corresponding mouse models to studies of the pathogenesis of this disease. Like other investigators [14, 15], we suggest that the term “HIES” best applies to patients with a phenotype of AD STAT3 deficiency.…”
Section: Introductionsupporting
confidence: 51%
See 1 more Smart Citation
“…We review here the history of HIES, and what is currently known about its three proposed genetic forms, and we discuss the contribution of the corresponding mouse models to studies of the pathogenesis of this disease. Like other investigators [14, 15], we suggest that the term “HIES” best applies to patients with a phenotype of AD STAT3 deficiency.…”
Section: Introductionsupporting
confidence: 51%
“…However, too few data are currently available to analyze the correlation of genotype with cellular and clinical phenotypes in patients. Surprisingly, measurements of residual PGM3 expression and function did not differentiate between the patients of these two cohorts [7-10, 14, 170, 171]. It would, nevertheless, be very interesting to compare the deleteriousness of biallelic PGM3 genotypes with that of various cellular, immunological, and clinical phenotypes.…”
Section: Pgm3 Deficiencymentioning
confidence: 99%
“…(9) Thus, a total of 23 patients from 11 families have been reported to have pathogenic PGM3 mutations. (1,2,4,8,9) Here we present two siblings with a skeletal dysplasia, severe combined immunodeficiency, bone marrow failure, renal malformations, and intestinal involvement, for whom we performed WES and found a new PGM3 mutation. We also compare the clinical features of our patients with the previously reported cases.…”
Section: Introductionmentioning
confidence: 91%
“…(1) The patient described by Lundin and colleagues presented eosinophilia and nearly normal to low values of neutrophils and T, B, and NK cells. (8) In mice carrying hypomorphic mutations in Pgm3, the anomalies included modest anemia and thrombocytopenia and severe reduction in B and T cells with an inverted CD4/CD8 ratio. (6) Stray-Pedersen and colleagues showed that hematopoietic stem cell transplant was efficient to cure the immune deficiency in 2 patients.…”
Section: Casementioning
confidence: 99%
“…PGM3 is an essential enzyme in the hexosamine biosynthetic pathway required for the production of UDP-GlcNAc (Willems, van Engelen, & Lefeber, 2016). Mutations in PGM3 were recently identified as causing an autosomal recessive immunodeficiency syndrome, combined with CDG phenotypic features (Lundin et al, 2015; Sassi et al, 2014; Stray-Pedersen et al, 2014; Zhang et al, 2014). As is the case with PGM1 deficiency, patient phenotypes in PGM3 deficiency are variable and complex.…”
Section: Biologymentioning
confidence: 99%